2009
DOI: 10.1016/j.ypmed.2008.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Working for health? Evidence from systematic reviews on the effects on health and health inequalities of organisational changes to the psychosocial work environment

Abstract: (2009) 'Working for health ? evidence from systematic reviews on the e ects on health and health inequalities of organisational changes to the psychosocial work environment.', Preventive medicine., 48 (5). pp. 454-461. Further information on publisher's website:http://dx.doi.org/10. 1016/j.ypmed.2008.12.018 Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 29 publications
2
69
0
4
Order By: Relevance
“…The quality of evidence from the systematic and scoping reviews was critically appraised using a checklist adapted and applied by experts in this methodology (Bambra et al 2009). Two researchers (DG, MC) independently analysed the quality of each review included in this umbrella review, obtaining a high level of concordance when comparing the results of the questions included in the critical appraisal.…”
Section: Ethnicity and Health 527mentioning
confidence: 99%
“…The quality of evidence from the systematic and scoping reviews was critically appraised using a checklist adapted and applied by experts in this methodology (Bambra et al 2009). Two researchers (DG, MC) independently analysed the quality of each review included in this umbrella review, obtaining a high level of concordance when comparing the results of the questions included in the critical appraisal.…”
Section: Ethnicity and Health 527mentioning
confidence: 99%
“…All these are 'moderator' dimensions of stress. Participatory cultural practices and enhancing employees' control (Egan et al, 2007) may particularly benefit disadvantaged groups, (Bambra et al, 2009) and were found likely to contribute to the development of a more empowering workplace culture of trust and learning (Lamontagne et al, 2007) and so assisting in making change sustainable (Giga et al, 2003;Kuoppala et al, 2008). An organization's culture has been defined as 'the specific collection of values and norms shared by people and groups in an organization that control the way they interact with each other.'…”
Section: Evidence Reviewmentioning
confidence: 99%
“…One optimal approach is through reducing workplace risk factors at organizational levels through policies and other practices (Bambra et al, 2009). The benefits for employers of implementing mental health promoting and prevention policies include increased productivity, recruitment, retention, and operational success along with decreased conflict and costs of disability and absenteeism (Standards Council of Canada, 2013).…”
Section: Introductionmentioning
confidence: 99%